Hepatitis C treatment completion rates in routine clinical care. - Butt, Adeel A; McGinnis, Kathleen A; Skanderson, Melissa; Justice, Amy C (Liver international : official journal of the International Association for the Study of the Liver, 2010)
Treatment completion rates for hepatitis C virus (HCV) infection in clinical practice settings are unknown.
Keywords: Antiviral Agents; Cohort Studies; Databases, Factual; Drug Therapy, Combination; Ethnic Groups; Female; Hepatitis C, Chronic; Humans; Interferon-alpha; Male; Medication Adherence; Middle Aged; Patient Dropouts; Polyethylene Glycols; Recombinant Proteins; Ribavirin; United States; Veterans